Etika dan Vandalisme Terselubung dalam Pemanfaatan Koleksi di Dinas Perpustakaan dan Kearsipan Provinsi Sumatera Utara - Zakira, Annisa Intan; Kharin, Haura Laudya; Maulina, Dina; Ajiziah, Zahrah; Ramadhani, Sri; Sembiring, Cherin Pebina (UI Scholars Hub, 2026)
This study addresses the prevalent issue of unethical user behavior towards library collections, which threatens their preservation. The main objective is to analyze the forms and underlying causes of these behaviors at the Library and Archives Service (Dispusip) of North Sumatra Province. This research employs a qualitative case study approach, utilizing direct observation, photographic documentation, and brief interviews as its methods. The results indicate a significant occurrence of unethical practices, such as page-folding (dog-earing), underlining or scribbling on pages, and mis-shelving books. These actions are categorized as “covert vandalism” and a lack of systemic awareness, stemming from a low sense of ethical responsibility among some users. Furthermore, the library’s efforts to foster user ethics are undermined by inconsistent policy communication, creating potential confusion. The study concludes that a gap exists between preservation goals and the cultivation of user ethics, recommending a shift towards proactive, consistent user education and harmonized policy communication.